Program Bersih-Bersih dan Pengecatan Lingkungan Sebagai Upaya Peningkatan Kualitas dan Estetika Kampus - Wakid Evendi; Muchamad Masrur; Didit Darmawan; Rahayu Mardikaningsih; Lailatul Faizah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aims to improve environmental cleanliness and the aesthetics of the area around the Sunan Giri University Surabaya campus, particularly in Janti Village. The method used in this activity was Participatory Action Research (PAR), which emphasizes active community involvement in every stage of the activity, from observation and planning to implementation. The activities included community service activities such as environmental cleanup, weed removal, drainage repair, road divider painting, and mural creation to beautify the environment. The results of the activity showed significant changes, both in terms of environmental cleanliness and increased public awareness and participation in maintaining the environment sustainably. The village environment became cleaner, more organized, and had better aesthetic value. Furthermore, residents took the initiative to maintain cleanliness independently. Thus, the PAR-based PkM activity has proven effective in encouraging positive change and empowering the Janti Village community towards better environmental management.